2003
DOI: 10.1167/iovs.03-0066
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Optokinetic Nystagmus and Saccades in Normal Human Subjects

Abstract: In this study, the best OK responses were obtained using stripes with lower spatial frequencies and lower stripe speeds (0.4 cyc/deg at 10 deg/s). The dynamic properties of vertical quick phases of nystagmus are similar enough to those of voluntary saccades for OK stimulation to be used as a clinical test of the vertical saccadic system in individuals with voluntary gaze palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…Children and adults who had infantile-onset strabismus may retain the deficit of downward OKN, as their up-down OKN asymmetries can exceed those of control subjects. 25,28,29 Our findings in the strabismic NHPs are similar. Each of the strabismic NHPs had upward OKN gains equivalent to-but downward OKN gains substantially less than-those of the control NHPs.…”
Section: Vertical Okn Asymmetrysupporting
confidence: 67%
See 2 more Smart Citations
“…Children and adults who had infantile-onset strabismus may retain the deficit of downward OKN, as their up-down OKN asymmetries can exceed those of control subjects. 25,28,29 Our findings in the strabismic NHPs are similar. Each of the strabismic NHPs had upward OKN gains equivalent to-but downward OKN gains substantially less than-those of the control NHPs.…”
Section: Vertical Okn Asymmetrysupporting
confidence: 67%
“…Garbutt et al 29 reported horizontal crosstalk during vertical OKN in strabismic adults. Their patients who had the classical stigmata of infantile-onset strabismus (LN and DVD, subjects 1-4) had weak downward OKN and the greatest crosstalk during downward OKN.…”
Section: Crosstalk and Directional Biases Of Horizontalvertical Oknmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation of the single threshold value, in cases in which only fixations and saccades are classified, is reported to substantially affect metrics such as number of detected saccades and fixations, average fixation duration, and saccade amplitude (Ceballos, Komogortsev, & Turner, 2009;Garbutt et al, 2003;Komogortsev, Gobert, Jayarathna, Koh, & Gowda, 2010;Poole & Ball, 2004). Frequently, researchers perform manual classification to avoid misidentification issues associated with automated algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Saccadic eye movements generally have short durations with only minor disturbances of the visual processing (Garbutt et al, 2003). These disturbances are prolonged in mature patients since eye-movement speed is significantly reduced.…”
Section: Regions In the Frontal Cerebral Cortexmentioning
confidence: 99%